Cell behaviour on micro-textured surfaces - Loh, Zhe Yuen. (2011)
The surface topology of materials can be modified to improve cell-surface interaction. While this has been done extensively by chemical means, mechanical modifications to surface topology are expected to also affect these interactions and therefore are considered worth investigating.